Oligo- and poly(fullerene)s for photovoltaic applications: Modeled electronic behaviors and synthesis - Santos Silva, Hugo; Ramanitra, Hasina H.; Bregadiolli, Bruna A. [UNESP]; Bégué, Didier; Graeff, Carlos F. O.; Dagron-Lartigau, Christine; Peisert, Heiko; Chassé, Thomas; Hiorns, Roger C. (Wiley, 2017)
The atom transfer radical addition polymerization (ATRAP) of fullerene to give poly(fullerene)s (PFs) for organic electronics is explored. Quantum chemistry maps the expected electronic behavior of PFs with respect to common electron acceptors, namely fullerene, phenyl-C61-butyric acid methyl ester and its bis-adduct, and mono- and bis-indine-fullerene derivatives. Surprisingly, it is found that PFs should demonstrate electron affinities and LUMO energy levels closer to the bis-derivatives than the mono-adducts, even though only one C60 double-bond is used in PF chain formation. A self-consistent library of PFs is synthesized and a correlation between structural characteristics and molecular weights is found. While comonomers with –OC16H33 linear side-chains lead to the highest known ATRAP molecular weights of 21000 g mol− 1, like-for-like, branched side-chains permit syntheses of higher molecular weights and more soluble polymers. Of the series, however, PFs with -OC12 side-chains are expected to be of the greatest interest for opto-electronic applications due to their ease of handling and highest regioregularity. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 1345–1355.
Keywords: atom transfer radical addition polymerization; fullerene; opto-electronic; poly(fullerene)s; structure-property relationship